Survey and Classification of Termite Species of Family Termitidae and their Locations in Nineveh Governorate - Wadhah Al-jebory; Nabil AL-Mallah (مجلة جامعة كركوك للعلوم الزراعية, 2023)
The results of the questionnaire for ten agricultural materials specialized in the control of the gnat insect in the center of Mosul, including the advisory office of the College of Agriculture and Forestry / University of Mosul (University of Mosul) in all neighborhoods and regions of the city of Mosul on its right and left sides, Some of these injuries were recent, while others were recorded in previous years  and that the degrees of infection or the level of presence of this insect among the neighborhoods of Mosul have Distributed between weak injury (1-3 houses / neighborhood), compensation (4-10 houses / neighborhood), and severe (more than 10 houses / neighborhood) , Where these ranges were developed based on the results of the questionnaire The highest average of infection for the right side of Mosul was for the neighborhoods of July 17, Al-Jawsaq, while the infection was weak in the neighborhoods of Al-Mamoun, Wadi Hajar, Al-Dawasa, Al-Nabi Sheet, Ras Al-Jada, Al-Zanjili, and Old Mosul. As for the areas of the left side, the highest average of infection was In the friendly neighborhoods, flowers, nationalization, Baath, Sumer, unity, charter, police, Arab, Palestine, banks, millions, finance, cultural group, University of Mosul. While the infection was weak in the neighborhoods of Aden, Al-Karamah, Jerusalem, Al-Intisar, Al-Salam, Nabi Younis, Algeria.                              The results of the field survey indicate that termites attack many different plants according to the areas included in the study, stalk namely Platan occidentalis trees (Mosul forests), stalk Silybum marianum bush (Hammam Al-Alil district), stalk sunflower crop Helianthus annuus (Bashiqa district), and fruit peel Cucumis melo (Cucumis melo) watermelon (Wana district). and the root tomato Solanum betaceum (Zummar district). The results of the diagnosis of termite samples sent to the Museum of Natural History at the University of Baghdad showed that all samples sent to different places where they were collected, the diagnosis proved that they belong to the species Microcerotermes diversus Silv. With the exception of sample No. (4) taken from the sunflower plant, Helianthus annuus, in the Al-Fadiliyah region of Bashiqa district, where it was of the type Amitermes villis Hagen.